The HSP40 chaperone Ydj1 drives amyloid beta 42 toxicity - Ring, Julia; Tadic, Jelena; Ristic, Selena; Poglitsch, Michael; Bergmann, Martina; Radic, Nemanja; Mossmann, Dirk; Liang, YongTian; Maglione, Marta; Jerkovic, Andrea; Hajiraissi, Roozbeh; Hanke, Marcel; et al. (EMBO Molecular Medicine)
Keywords: Molecular Medicine

Metamodellbasierte Prozesskette - Umformen-Schneiden-Spannen-Fügen - Heyser, Per; Meschut, Gerson; Nehls, Thomas; Scharr, Christian; Froitzheim, Pascal; Flügge, Wilko; Wiesenmayer, Sebastian; Merklein, Marion (Pressen, Systeme, Prozesse der Zukunft Effizienz + Digitalisierung)

Konzeption einer adaptiven Prozesskette für das mechanische Fügen - Meschut, Gerson; Heyser, Per; Merklein, Marion; Wiesenmayer, Sebastian; Flügge, Wilko; Scharr, Christian; Nehls, Thomas

Smart process chain – data analysis in sheet metal processing for joinability prediction - Heyser, Per; Wiesenmayer, Sebastian; Nehls, Thomas; Scharr, Christian; Flügge, Wilko; Merklein, Marion; Meschut, Gerson (SMART PRODUCTION 2022: DIGITALIZING AUTOMOTIVE MANUFACTURING)

Investigating the argumentation structures of EFL learners from diverse language backgrounds - Chen, Mei-Hua; Mudgal, Garima; Chen, Wei-Fan; Wachsmuth, Henning (EUROCALL)

Entwicklung eines innovativen Trennapparates zur Stickstoffrückgewinnung aus landwirtschaftlichen Abfällen - Bernemann, Sören Antonius; Maćkowiak, Jan; Maćkowiak, Jerzy; Bertling, René; Lutters, Nicole; Kenig, Eugeny

Stress-Aware Periodic Test of Interconnects - Sadeghi-Kohan, Somayeh; Hellebrand, Sybille; Wunderlich, Hans-Joachim (Journal of Electronic Testing)
Safety-critical systems have to follow extremely high dependability requirements as specified in the standards for automotive, air, and space applications. The required high fault coverage at runtime is usually obtained by a combination of concurrent error detection or correction and periodic tests within rather short time intervals. The concurrent scheme ensures the integrity of computed results while the periodic test has to identify potential aging problems and to prevent any fault accumulation which may invalidate the concurrent error detection mechanism. Such periodic built-in self-test (BIST) schemes are already commercialized for memories and for random logic. The paper at hand extends this approach to interconnect structures. A BIST scheme is presented which targets interconnect defects before they will actually affect the system functionality at nominal speed. A BIST schedule is developed which significantly reduces aging caused by electromigration during the lifetime application of the periodic test.
Keywords: Electrical and Electronic Engineering

EM-Aware Interconnect BIST - Sadeghi-Kohan, Somayeh; Hellebrand, Sybille; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

Low Areal Densities of InAs Quantum Dots on GaAs(100) Prepared by Molecular Beam Epitaxy - Verma, A.K.; Bopp, F.; Finley, J.J.; Jonas, B.; Zrenner, A.; Reuter, Dirk (Journal of Crystal Growth)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Procrastination in the Looking Glass of Self-Awareness: Can Gamified Self-Monitoring Reduce Academic Procrastination? - Klingsiek, Katrin; John, Thomas; Kundisch, Dennis (die hochschullehre)

Does it really take a village to raise a child? Reflections on the need for collective responsibility in inclusive education - Subban, Pearl K.; Bradford, Brent; Sharma, Umesh; Loreman, Tim; Avramidis, Elias; Kullmann, Harry; Sahli Lozano, Caroline; Romano, Alessandra; Woodcock, Stuart (European Journal of Special Needs Education)

Broadband optical Ta2O5 antennas for directional emission of light - Farheen, Henna; Yan, Lok-Yee; Quiring, Viktor; Eigner, Christof; Zentgraf, Thomas; Linden, Stefan; Förstner, Jens; Myroshnychenko, Viktor (Optics Express)
Highly directive antennas with the ability of shaping radiation patterns in desired directions are essential for efficient on-chip optical communication with reduced cross talk. In this paper, we design and optimize three distinct broadband traveling-wave tantalum pentoxide antennas exhibiting highly directional characteristics. Our antennas contain a director and reflector deposited on a glass substrate, which are excited by a dipole emitter placed in the feed gap between the two elements. Full-wave simulations in conjunction with global optimization provide structures with an enhanced linear directivity as high as 119 radiating in the substrate. The high directivity is a result of the interplay between two dominant TE modes and the leaky modes present in the antenna director. Furthermore, these low-loss dielectric antennas exhibit a near-unity radiation efficiency at the operational wavelength of 780 nm and maintain a broad bandwidth. Our numerical results are in good agreement with experimental measurements from the optimized antennas fabricated using a two-step electron-beam lithography, revealing the highly directive nature of our structures. We envision that our antenna designs can be conveniently adapted to other dielectric materials and prove instrumental for inter-chip optical communications and other on-chip applications.
Keywords: tet_topic_opticalantenna

Dekonstruktionen des Staatssozialismus (und mehr). Komische Helden der Wende- und Nachwendezeit in deutschsprachiger Literatur - Elit, Stefan (Aufbruch und Krise. Ästhetische/Narrative Auseinandersetzungen mit der spanischen Transición und der deutschen ‚Wende‘ (Germanisch-Romanische Monatsschrift. Beiheft))

Exploration of Location Data: Real Data in the Context of Interaction with a Cellular Network - Höper, Lukas; Podworny, Susanne; Schulte, Carsten; Frischemeier, Daniel (Proceedings of the IASE 2021 Satellite Conference)
Students are not aware and have little understanding of collecting and processing personal data in their everyday contexts of interaction with data-driven digital artifacts. To be aware of where, how and why data are collected and processed is important to be self-determined. Therefore, we develop and evaluate a teaching sequence to provide reasoning about data as a fundamental aspect of statistical literacy. This teaching sequences deals with the context of interaction with a cellular network where location data are collected. Students get real location data from an unknown person which can be explored with the aim to characterize the person. Students gain different insights by using different basic filters and explain how they achieve these. The results of the exploratory study indicate that students learned to gain insights by exploring given location data and that these insights may describe the person with detailed aspects that may not necessarily be true.

Experimental verification of the acoustic geometric phase - Liu, Bingyi; Zhou, Zhiling; Wang, Yongtian; Zentgraf, Thomas; Li, Yong; Huang, Lingling (Applied Physics Letters)
Optical geometric phase encoded by in-plane spatial orientation of microstructures has promoted the rapid development of numerous functional meta-devices. However, pushing the concept of the geometric phase toward the acoustic community still faces challenges. In this work, we utilize two acoustic nonlocal metagratings that could support a direct conversion between an acoustic plane wave and a designated vortex mode to obtain the acoustic geometric phase, in which an orbital angular momentum conversion process plays a vital role. In addition, we realize the acoustic geometric phases of different orders by merely varying the orientation angle of the acoustic nonlocal metagratings. Intriguingly, according to our developed theory, we reveal that the reflective acoustic geometric phase, which is twice the transmissive one, can be readily realized by transferring the transmitted configuration to a reflected one. Both the theoretical study and experimental measurements verify the announced transmissive and reflective acoustic geometric phases. Moreover, the reconfigurability and continuous phase modulation that covers the 2π range shown by the acoustic geometric phases provide us with the alternatives in advanced acoustic wavefront control.
Keywords: Physics and Astronomy (miscellaneous)

Mincut Sensitivity Data Structures for the Insertion of an Edge - Baswana, Surender; Gupta, Shiv; Knollmann, Till (Algorithmica)
Keywords: Applied Mathematics; Computer Science Applications; General Computer Science

Friedrich Gottlieb Klopstock: Handexemplar der „Oden“. Kritische Edition, hg. v. Marit Müller, Göttingen 2020 (edition Text 18) - Elit, Stefan (Arbitrium 40)

Giant Photoelasticity of Polaritons for Detection of Coherent Phonons in a Superlattice with Quantum Sensitivity - Kobecki, Michal; Scherbakov, Alexey V.; Kukhtaruk, Serhii M.; Yaremkevich, Dmytro D.; Henksmeier, Tobias; Trapp, Alexander; Reuter, Dirk; Gusev, Vitalyi E.; Akimov, Andrey V.; Bayer, Manfred (Physical Review Letters)
Keywords: General Physics and Astronomy

Kronecker Decomposition for Knowledge Graph Embeddings - Demir, Caglar; Lienen, Julian; Ngonga Ngomo, Axel-Cyrille (arXiv:2205.06560)
Knowledge graph embedding research has mainly focused on learning continuous representations of entities and relations tailored towards the link prediction problem. Recent results indicate an ever increasing predictive ability of current approaches on benchmark datasets. However, this effectiveness often comes with the cost of over-parameterization and increased computationally complexity. The former induces extensive hyperparameter optimization to mitigate malicious overfitting. The latter magnifies the importance of winning the hardware lottery. Here, we investigate a remedy for the first problem. We propose a technique based on Kronecker decomposition to reduce the number of parameters in a knowledge graph embedding model, while retaining its expressiveness. Through Kronecker decomposition, large embedding matrices are split into smaller embedding matrices during the training process. Hence, embeddings of knowledge graphs are not plainly retrieved but reconstructed on the fly. The decomposition ensures that elementwise interactions between three embedding vectors are extended with interactions within each embedding vector. This implicitly reduces redundancy in embedding vectors and encourages feature reuse. To quantify the impact of applying Kronecker decomposition on embedding matrices, we conduct a series of experiments on benchmark datasets. Our experiments suggest that applying Kronecker decomposition on embedding matrices leads to an improved parameter efficiency on all benchmark datasets. Moreover, empirical evidence suggests that reconstructed embeddings entail robustness against noise in the input knowledge graph. To foster reproducible research, we provide an open-source implementation of our approach, including training and evaluation scripts as well as pre-trained models in our knowledge graph embedding framework.

Anion-specific structure and stability of guanidinium-bound DNA origami - Hanke, Marcel; Dornbusch, Daniel; Hadlich, Christoph; Rossberg, Andre; Hansen, Niklas; Grundmeier, Guido; Tsushima, Satoru; Keller, Adrian; Fahmy, Karim (Computational and Structural Biotechnology Journal)
Keywords: Computer Science Applications; Genetics; Biochemistry; Structural Biology; Biophysics; Biotechnology

Conformal Credal Self-Supervised Learning - Lienen, Julian; Demir, Caglar; Hüllermeier, Eyke (arXiv:2205.15239)
In semi-supervised learning, the paradigm of self-training refers to the idea of learning from pseudo-labels suggested by the learner itself. Across various domains, corresponding methods have proven effective and achieve state-of-the-art performance. However, pseudo-labels typically stem from ad-hoc heuristics, relying on the quality of the predictions though without guaranteeing their validity. One such method, so-called credal self-supervised learning, maintains pseudo-supervision in the form of sets of (instead of single) probability distributions over labels, thereby allowing for a flexible yet uncertainty-aware labeling. Again, however, there is no justification beyond empirical effectiveness. To address this deficiency, we make use of conformal prediction, an approach that comes with guarantees on the validity of set-valued predictions. As a result, the construction of credal sets of labels is supported by a rigorous theoretical foundation, leading to better calibrated and less error-prone supervision for unlabeled data. Along with this, we present effective algorithms for learning from credal self-supervision. An empirical study demonstrates excellent calibration properties of the pseudo-supervision, as well as the competitiveness of our method on several benchmark datasets.

Stress-based fatigue lifetime prediction of adhesively bonded joints with hyperelastic deformation behavior - Çavdar, Serkan; Meschut, Gerson (45th Annual Meeting of The Adhesion Society)

Computation and analysis of Pareto critical sets in smooth and nonsmooth multiobjective optimization - Gebken, Bennet
Mehrzieloptimierung behandelt Probleme, bei denen mehrere skalare Zielfunktionen simultan optimiert werden sollen. Ein Punkt ist in diesem Fall optimal, wenn es keinen anderen Punkt gibt, der mindestens genauso gut ist in allen Zielfunktionen und besser in mindestens einer Zielfunktion. Ein notwendiges Optimalitätskriterium lässt sich über Ableitungsinformationen erster Ordnung der Zielfunktionen herleiten. Die Menge der Punkte, die dieses notwendige Kriterium erfüllen, wird als Pareto-kritische Menge bezeichnet. Diese Arbeit enthält neue Resultate über Pareto-kritische Mengen für glatte und nicht-glatte Mehrzieloptimierungsprobleme, sowohl was deren Berechnung betrifft als auch deren Struktur. Im glatten Fall erfolgt die Berechnung über ein Fortsetzungsverfahren, im nichtglatten Fall über ein Abstiegsverfahren. Anschließend wird die Struktur des Randes der Pareto-kritischen Menge analysiert, welcher aus Pareto-kritischen Mengen kleinerer Subprobleme besteht. Schlussendlich werden inverse Probleme betrachtet, bei denen zu einer gegebenen Datenmenge ein Zielfunktionsvektor gefunden werden soll, für den die Datenpunkte kritisch sind.

Negative polarization of light at backscattering from a numerical analog of planetary regoliths - Grynko, Yevgen; Shkuratov, Yuriy; Alhaddad, Samer; Förstner, Jens (Icarus)
We model negative polarization, which is observed for planetary regoliths at backscattering, solving a full wave problem of light scattering with a numerically exact Discontinuous Galerkin Time Domain (DGTD) method. Pieces of layers with the bulk packing density of particles close to 0.5 are used. The model particles are highly absorbing and have irregular shapes and sizes larger than the wavelength of light. This represents a realistic analog of low-albedo planetary regoliths. Our simulations confirm coherent backscattering mechanism of the origin of negative polarization. We show that angular profiles of polarization are stabilized if the number of particles in a layer piece becomes larger than ten. This allows application of our approach to the negative polarization modeling for planetary regoliths.
Keywords: tet_topic_scattering

"Elizabeth Grubgeld, Disability and Life Writing in Post-Independence Ireland", Book Review - Strauß, Sara (European Journal of Life Writing)

Anticipating Expectations. Family Language Policy and its Orientation to the School System - Ballweg, Sandra (International Journal of Multilingualims)

Transitivitätscharakteristika als Werkzeug in der systematischen qualitativen Metaphernanalyse - Karsten, Andrea; Schwede, Jana; Körber, Miriam; Scharlau, Ingrid (Die Praxis der systematischen Metaphernanalyse)

Combined Effects of Uniform Applied Pressure and Electrolyte Additives in Lithium-Metal Batteries - Kasse, Robert M.; Geise, Natalie R.; Sebti, Elias; Lim, Kipil; Takacs, Christopher J.; Cao, Chuntian; Steinrück, Hans-Georg; Toney, Michael F. (ACS Applied Energy Materials)
Keywords: Electrical and Electronic Engineering; Materials Chemistry; Electrochemistry; Energy Engineering and Power Technology; Chemical Engineering (miscellaneous)

Detecting Data Incompatibilities in Process-Driven Decision Support Systems - Kirchhoff, Jonas; Gottschalk, Sebastian; Engels, Gregor (Lecture Notes in Business Information Processing)
Decision makers in complex business environments have different goals and constraints and therefore require tailored decision support systems (DSS). Following a low-code approach, a tailored DSS can be created by a decision maker as a process-based composition of existing, interoperable decision support services. Data incompatibilities may be introduced during the design or execution of such a process-driven DSS, e.g., when a service always generates or a decision maker selects data which violates a data constraint of a subsequent service. These incompatibilities cause interrupted or erroneous decision processes. In this paper, we contribute an approach which enables the detection of data incompatibilities in process-driven DSS during process design and execution. Our approach utilizes the JSON Schema specification to define service interfaces and associated type constraints which data produced by services or decision makers can be validated against. We demonstrate our approach in the context of decision support for energy network planning using a prototypical open-source implementation.

Speaking of Performance: Evaluating Team Members’ Performance with Open-Ended Audio Comments - Gutt, Jana Kim; Thommes, Kirsten (Academy of Management Proceedings)
Keywords: Microbiology

In-Mold-Assembly of Hybrid Bending Structures by Compression Molding - Stallmeister, Tim; Tröster, Thomas (Key Engineering Materials)
The further development of in-mold-assembly (IMA) technologies for structural hybrid components is of great importance for increasing the economic efficiency and thus the application potential. This paper presents an innovative IMA process concept for the manufacturing of bending loaded hybrid components consisting of two outer metal belts and an inner core structure made of glass mat reinforced thermoplastic (GMT). In this process, the core structure, which is provided with stiffening ribs and functional elements, is formed and joined to two metal belts in one single step. For experimental validation of the concept, the development of a prototypic molding tool and the manufacturing of hybrid beams including process parameters are described. Three-point bending tests and optical measurement technologies are used to characterize the failure behavior and mechanical properties of the produced hybrid beams. It was found that the innovative IMA process enables the manufacturing of hybrid components with high energy absorption and low weight in one step. The mass-specific energy absorption is increased by 693 % compared to pure GMT beams.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Shifting ML value creation mechanisms: A process model of ML value creation - Shollo, Arisa; Hopf, Konstantin; Thiess, Tiemo; Müller, Oliver (The Journal of Strategic Information Systems)
Keywords: Information Systems and Management; Information Systems; Management Information Systems

Direct visualization of the drug loading of single DNA origami nanostructures by AFM-IR nanospectroscopy - Hanke, Marcel; Grundmeier, Guido; Keller, Adrian (Nanoscale)
The efficient loading of DNA nanostructures with intercalating or groove-binding drugs is an important prerequisite for various applications in drug delivery. However, unambiguous verification and quantification of successful drug loading...
Keywords: General Materials Science

Sauber recyceln- Innovative Verfahrenskombination mit Ultraschall ermöglicht sicheren Umgang mit recycelten Carbonfasern - Linnig, Caterina; Tröster, Thomas (CU reports)

Dietary protein intake and health-related outcomes: a methodological protocol for the evidence evaluation and the outline of an evidence to decision framework underlying the evidence-based guideline of the German Nutrition Society - Kroke, Anja; Schmidt, Annemarie; Amini, Anna M.; Kalotai, Nicole; Lehmann, Andreas; Haardt, Julia; Bauer, Jürgen M.; Bischoff-Ferrari, Heike A.; Boeing, Heiner; Egert, Sarah; Ellinger, Sabine; Kühn, Tilman; et al. (European Journal of Nutrition)
Abstract Purpose The present work aimed to delineate (i) a revised protocol according to recent methodological developments in evidence generation, to (ii) describe its interpretation, the assessment of the overall certainty of evidence and to (iii) outline an Evidence to Decision framework for deriving an evidence-based guideline on quantitative and qualitative aspects of dietary protein intake. Methods A methodological protocol to systematically investigate the association between dietary protein intake and several health outcomes and for deriving dietary protein intake recommendations for the primary prevention of various non-communicable diseases in the general adult population was developed. Results The developed methodological protocol relies on umbrella reviews including systematic reviews with or without meta-analyses. Systematic literature searches in three databases will be performed for each health-related outcome. The methodological quality of all selected systematic reviews will be evaluated using a modified version of AMSTAR 2, and the outcome-specific certainty of evidence for systematic reviews with or without meta-analysis will be assessed with NutriGrade. The general outline of the Evidence to Decision framework foresees that recommendations in the derived guideline will be given based on the overall certainty of evidence as well as on additional criteria such as sustainability. Conclusion The methodological protocol permits a systematic evaluation of published systematic reviews on dietary protein intake and its association with selected health-related outcomes. An Evidence to Decision framework will be the basis for the overall conclusions and the resulting recommendations for dietary protein intake.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Concept Study of an LLC Converter with Magnetically Resonant Inductor - Böcker, Joachim (2022 International Symposium on Power Electronics, Electrical Drives, Automation and Motion (SPEEDAM))

Combined Ranking and Regression Trees for Algorithm Selection - Fehring, Lukas

Untersuchung der physikalische Absorptionsmethoden zur Bestimmung von gasseitigen Stoffübergangskoeffizienten für strukturierte Packungen basierend auf hydrodynamischen Analogien - Luan, Yunhao

Hexenverhörprotokolle als sprachhistorisches Korpus. Fallstudien zur Erschließung der frühneuzeitlichen Schriftsprache - Markewitz, Friedrich (Zeitschrift für Angewandte Linguistik)

Generation of a Reduced, Representative, Virtual Test Drive for Fast Evaluation of Tire Wear by Clustering of Driving Data - Muth, Lars; Noll, Christian; Sextro, Walter (Advances in Dynamics of Vehicles on Roads and Tracks II - Proceedings of the 27th Symposium of the International Association of Vehicle System Dynamics, IAVSD 2021)
Tire and road wear are a major source of emissions of nonexhaust particulate matter (PM) and make up the largest share of microplastics in the environment. To reduce tire wear through numerical optimization of a vehicle's suspension system, fast simulations of the representative usage of a vehicle are needed. Therefore, this contribution evaluates if instead of a full simulation of a representative test drive, only specific driving maneuvers resulting from a clustering of the driving data can be used to predict tire wear. As a measure for tire wear, the friction work between tire and road is calculated. It is shown that enough clusters result in negligible deviations between the total friction work of the full simulation and the cluster simulations as well as between the distributions of the friction work over the tire width. The calculation time can be reduced to about 1% of the full simulation.
Keywords: Tire Wear; Vehicle Dynamics; Clustering; Virtual Test

Machine Learning for Online Algorithm Selection under Censored Feedback - Tornede, Alexander; Bengs, Viktor; Hüllermeier, Eyke (Proceedings of the 36th AAAI Conference on Artificial Intelligence)
In online algorithm selection (OAS), instances of an algorithmic problem class are presented to an agent one after another, and the agent has to quickly select a presumably best algorithm from a fixed set of candidate algorithms. For decision problems such as satisfiability (SAT), quality typically refers to the algorithm's runtime. As the latter is known to exhibit a heavy-tail distribution, an algorithm is normally stopped when exceeding a predefined upper time limit. As a consequence, machine learning methods used to optimize an algorithm selection strategy in a data-driven manner need to deal with right-censored samples, a problem that has received little attention in the literature so far. In this work, we revisit multi-armed bandit algorithms for OAS and discuss their capability of dealing with the problem. Moreover, we adapt them towards runtime-oriented losses, allowing for partially censored data while keeping a space- and time-complexity independent of the time horizon. In an extensive experimental evaluation on an adapted version of the ASlib benchmark, we demonstrate that theoretically well-founded methods based on Thompson sampling perform specifically strong and improve in comparison to existing methods.

Algorithm Selection on a Meta Level - Tornede, Alexander; Gehring, Lukas; Tornede, Tanja; Wever, Marcel Dominik; Hüllermeier, Eyke (Machine Learning)
The problem of selecting an algorithm that appears most suitable for a specific instance of an algorithmic problem class, such as the Boolean satisfiability problem, is called instance-specific algorithm selection. Over the past decade, the problem has received considerable attention, resulting in a number of different methods for algorithm selection. Although most of these methods are based on machine learning, surprisingly little work has been done on meta learning, that is, on taking advantage of the complementarity of existing algorithm selection methods in order to combine them into a single superior algorithm selector. In this paper, we introduce the problem of meta algorithm selection, which essentially asks for the best way to combine a given set of algorithm selectors. We present a general methodological framework for meta algorithm selection as well as several concrete learning methods as instantiations of this framework, essentially combining ideas of meta learning and ensemble learning. In an extensive experimental evaluation, we demonstrate that ensembles of algorithm selectors can significantly outperform single algorithm selectors and have the potential to form the new state of the art in algorithm selection.

Verbessertes Füllverhalten im Spritzgießprozess durch Schäumen von WPC: Bewertung des Fließverhaltens treibmittelbeladener Polymerschmelzen - Fuhrmann, Anika; Schoch, Rebecca; Rusam, Alexander; Bosse, Michael; Flachmann, Felix; Moritzer, Elmar; Hochrein, Thomas; Bastian, Martin

A comparison of heuristic, statistical, and machine learning methods for heated tool butt welding of two different materials - Gevers, Karina; Tornede, Alexander; Wever, Marcel Dominik; Schöppner, Volker; Hüllermeier, Eyke (Welding in the World)
Abstract Heated tool butt welding is a method often used for joining thermoplastics, especially when the components are made out of different materials. The quality of the connection between the components crucially depends on a suitable choice of the parameters of the welding process, such as heating time, temperature, and the precise way how the parts are then welded. Moreover, when different materials are to be joined, the parameter values need to be tailored to the specifics of the respective material. To this end, in this paper, three approaches to tailor the parameter values to optimize the quality of the connection are compared: a heuristic by Potente, statistical experimental design, and Bayesian optimization. With the suitability for practice in mind, a series of experiments are carried out with these approaches, and their capabilities of proposing well-performing parameter values are investigated. As a result, Bayesian optimization is found to yield peak performance, but the costs for optimization are substantial. In contrast, the Potente heuristic does not require any experimentation and recommends parameter values with competitive quality.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Multi-Objective Trust-Region Filter Method for Nonlinear Constraints using Inexact Gradients - Berkemeier, Manuel Bastian; Peitz, Sebastian (arXiv:2208.12094)
In this article, we build on previous work to present an optimization algorithm for nonlinearly constrained multi-objective optimization problems. The algorithm combines a surrogate-assisted derivative-free trust-region approach with the filter method known from single-objective optimization. Instead of the true objective and constraint functions, so-called fully linear models are employed and we show how to deal with the gradient inexactness in the composite step setting, adapted from single-objective optimization as well. Under standard assumptions, we prove convergence of a subset of iterates to a quasi-stationary point and if constraint qualifications hold, then the limit point is also a KKT-point of the multi-objective problem.

Differences in NPI strategies against COVID-19 - Redlin, Margarete (Journal of Regulatory Economics)
Abstract Non-pharmaceutical interventions are an effective strategy to prevent and control COVID-19 transmission in the community. However, the timing and stringency to which these measures have been implemented varied between countries and regions. The differences in stringency can only to a limited extent be explained by the number of infections and the prevailing vaccination strategies. Our study aims to shed more light on the lockdown strategies and to identify the determinants underlying the differences between countries on regional, economic, institutional, and political level. Based on daily panel data for 173 countries and the period from January 2020 to October 2021 we find significant regional differences in lockdown strategies. Further, more prosperous countries implemented milder restrictions but responded more quickly, while poorer countries introduced more stringent measures but had a longer response time. Finally, democratic regimes and stronger manifested institutions alleviated and slowed down the introduction of lockdown measures.
Keywords: Economics and Econometrics

Modelling artificial intelligence in economics - Gries, Thomas; Naudé, Wim (Journal for Labour Market Research)
Abstract We provide a partial equilibrium model wherein AI provides abilities combined with human skills to provide an aggregate intermediate service good. We use the model to find that the extent of automation through AI will be greater if (a) the economy is relatively abundant in sophisticated programs and machine abilities compared to human skills; (b) the economy hosts a relatively large number of AI-providing firms and experts; and (c) the task-specific productivity of AI services is relatively high compared to the task-specific productivity of general labor and labor skills. We also illustrate that the contribution of AI to aggregate productive labor service depends not only on the amount of AI services available but on the endogenous number of automated tasks, the relative productivity of standard and IT-related labor, and the substitutability of tasks. These determinants also affect the income distribution between the two kinds of labor. We derive several empirical implications and identify possible future extensions.
Keywords: General Medicine

Local Mutual Exclusion for Dynamic, Anonymous, Bounded Memory Message Passing Systems - Daymude, Joshua J.; Richa, Andréa W.; Scheideler, Christian (1st Symposium on Algorithmic Foundations of Dynamic Networks, SAND 2022, March 28-30, 2022, Virtual Conference)

The Market for Belief Systems: A Formal Model of Ideological Choice - Gries, Thomas; Müller, Veronika; Jost, John T. (Psychological Inquiry)
Keywords: General Psychology

Einbettung von Augmented Reality in den Experimentierprozess - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Unsicherheit als Element von naturwissenschaftsbezogenen Bildungsprozessen)
Keywords: augmented reality; modelle; digitale Medien

»Fachspezifisches Chinesisch« an der Universität Paderborn - Hambach, Dennis (Handbuch China-Kompetenzen)
Das Programm Maschinenbau in China (mb-cn) ist eine spezielle Ausprägung der Paderborner Masterstudiengänge Maschinenbau, Wirtschafts- und Chemieingenieurwesen. Im Rahmen dieses Programms wird der technisch-interkulturelle Fachsprachkurs »Fachspezifisches Chinesisch« angeboten, der die praktische Anwendung des Sprachenlernens mit studiengangsbezogenen Angeboten kombiniert. Ziel des Kurses ist es, die Studierenden zu befähigen eine Hanyu-Shuiping-Kaoshi-Prüfung (HSK) auf Niveaustufe 2 zu bestehen sowie ihnen vertiefendes Fachvokabular aus den Fachbereichen Mathematik, Informatik, Wirtschaft, Technik und Maschinenbau zu vermitteln. Ausgewählte Beispiele in der fachsprachlichen Anwendung beziehensich auf die Beschreibung eines Gegenstandes wie den Getriebeaufbau und das Wirkprinzip eines Prüfstandes. Der Artikel soll als Evaluation und Rückschau auf das Pilotprojekt der Universität Paderborn dienen und Hilfestellung geben, wie die Konzeption und Umsetzung (auch unter Coronabedingungen) gelingen kann.

Maschinenbau in China - Denzer, Vera; Hambach, Dennis (Handbuch China-Kompetenzen)
Das seit den 1990er Jahren andauernde Engagement der Universität Paderborn in China hat zur Ausbildung von technisch-interkultureller China-Kompetenz in vielen Bereichengeführt. Die Universität Paderborn (UPB) unterhält derzeit sechs intensive Austauschpartnerschaften mit chinesischen Hochschulen. Im Rahmen der Masterstudiengänge Maschinenbau, Wirtschafts- und Chemieingenieurwesen sowie Wirtschaftsingenieurwesen wird die Studienausrichtung Maschinenbau in China (mb-cn) angeboten. Diese Studienausrichtung wird inenger Zusammenarbeit mit namhaften, global agierenden Partnerfirmen durchgeführt, die eigene Tochterfirmen in China oder eine starke Verbindung zu chinesischen Unternehmen haben. Zusätzlich können die Studierenden ein Fachpraktikum in einem deutschen Unternehmen in China absolvieren. Im Rahmen des Artikels wird das mb-cn-Projekt ausführlich vorgestellt. Die hierbeigeschilderten Erfahrungen mit dem Aufbau der Kooperation sowie die gezogenen Rückschlüsse auf die Ergebnisse des Projekts sollen dazu dienen, andere Einrichtungen beim Aufbau ähnlicher Kooperation zu unterstützen.

Brief Announcement: The (Limited) Power of Multiple Identities: Asynchronous Byzantine Reliable Broadcast with Improved Resilience through Collusion - Götte, Thorsten; Scheideler, Christian (SPAA ’22: 34th ACM Symposium on Parallelism in Algorithms and Architectures, Philadelphia, PA, USA, July 11 - 14, 2022)

Medienbildung als Radikalisierungsprävention? - Herzig, Bardo (Radikalisierungsnarrative online. Perspektiven und Lehren aus Wissenschaft und Prävention)

Lehren und Lernen mit (digitalen) Medien im Pädagogikunterricht - Herzig, Bardo; Martin, Alexander (Handbuch Pädagogikunterricht)

Identification of piezoelectric material parameters using optimised multi-electrode specimens - Claes, Leander; Feldmann, Nadine; Schulze, Veronika; Jurgelucks, Benjamin; Walther, Andrea; Henning, Bernd (Fortschritte der Akustik - DAGA 2022)

PLS-Based Structural Equation Modelling: An Alternative Approach to Estimating Complex Relationships Between Unobserved Constructs - Goller, Michael; Hilkenmeier, Frederic (Methods for Researching Professional Learning and Development)

Addressing Methodological Challenges in Research on Professional Learning and Development - Goller, Michael; Kyndt, Eva; Paloniemi, Susanna; Damşa, Crina (Methods for Researching Professional Learning and Development)

Q Method: Assessing Subjectivity Through Structured Ranking of Items - Leidig, Susann; Köhler, Hanna; Caruso, Carina; Goller, Michael (Methods for Researching Professional Learning and Development)

Participant’s Video Annotations as a Database to Measure Professional Development - Steffen, Bianca; Pouta, Maikki (Methods for Researching Professional Learning and Development)

Uncovering Informal Workplace Learning by Using Diaries - Rausch, Andreas; Goller, Michael; Steffen, Bianca (Methods for Researching Professional Learning and Development)

Delphi-Technique as a Method for Research on Professional Learning - Harteis, Christian (Methods for Researching Professional Learning and Development)

Kompetenzerwerb auf der Schulstation: Eine Mixed-Methods-Replikationsstudie - Goller, Michael; Steffen, Bianca; Lau, D. (Professionalisierung der Gesundheitsberufe. Berufliche und hochschulische Bildung im Spiegel aktueller Forschung)

Essays on Industrial Organization and Networks: Retail Bundling, Exclusive Dealing, and Network Disruption - Endres-Fröhlich, Angelika Elfriede

Methods for Researching Professional Learning and Development

Decision Support Ecosystems: Deﬁnition and Platform Architecture - Kirchhoff, Jonas; Weskamp, Christoph; Engels, Gregor (Decision Support Systems XII: Decision Support Addressing Modern Industry, Business, and Societal Needs)
Decision support systems are crucial in helping decision makers to quickly identify optimal business decisions in increasingly volatile and complex business environments. However, the ideal DSS for one decision maker may not optimally address the requirements for decision support of another decision maker. This is due to differences between decision makers in business goals, regulatory restrictions or availability of resources such as data. By using a suboptimal DSS, decision makers risk implementing suboptimal decision recommendations which endanger the success of their business. This presents DSS developers with the challenge to implement a customizable DSS which can be tailored to the individual requirements for decision support of a single decision maker. In order to address this challenge, we suggest a decision support ecosystem in which DSS developers, decision makers and other domain experts collaborate using a shared platform to provide and combine reusable decision support services into a tailored DSS. The contribution of our paper is twofold: First, we define the concept of a decision support ecosystem with respect to existing digital business ecosystems and discuss expected benefits and challenges. Second, we present a reference architecture for a shared platform supporting the realization of a decision support ecosystem. We demonstrate our contributions in the example application domain of regional energy distribution network planning.

Requirements-Based Composition of Tailored Decision Support Systems - Kirchhoff, Jonas; Weskamp, Christoph; Engels, Gregor (Human-Centered Software Engineering)
Corporate decision makers have individual requirements for decision support influenced by business goals, regulatory restrictions or access to resources such as data. Ideally, decision makers could quickly create tailored decision support systems (DSS) themselves which optimally address their individual requirements for decision support. Although service-oriented architectures have been proposed for DSS customization, they are primarily targeting trained software developers and cannot immediately be adapted by decision makers or domain experts with little to no software development knowledge. In this paper, we therefore motivate an assisted process-based service composition approach which can be used by non-developers to create tailored DSS. For assistance during service composition, we contribute a meta-model for the formalization of both decision support requirements and functionality of decision support services. Models created according to the meta-model can be used to detect mismatches between a decision maker’s requirements for decision support and services selected in the service composition representing a DSS. Furthermore, the formalizations may even be used for automated service composition given a decision maker’s decision support requirements. We demonstrate the expressiveness of our meta-model in the domain of regional energy distribution network planning.

Amplified steady state bifurcations in feedforward networks - von der Gracht, Sören; Nijholt, Eddie; Rink, Bob (Nonlinearity)
We investigate bifurcations in feedforward coupled cell networks. Feedforward structure (the absence of feedback) can be defined by a partial order on the cells. We use this property to study generic one-parameter steady state bifurcations for such networks. Branching solutions and their asymptotics are described in terms of Taylor coefficients of the internal dynamics. They can be determined via an algorithm that only exploits the network structure. Similar to previous results on feedforward chains, we observe amplifications of the growth rates of steady state branches induced by the feedforward structure. However, contrary to these earlier results, as the interaction scenarios can be more complicated in general feedforward networks, different branching patterns and different amplifications can occur for different regions in the space of Taylor coefficients.
Keywords: Applied Mathematics; General Physics and Astronomy; Mathematical Physics; Statistical and Nonlinear Physics

Influence of Screw Design on Fiber Breakage of Glass Fiber Reinforced Polypropylene in the Injection Molding Process - Moritzer, Elmar; Bürenhaus, Franziska Isabelle (37th International Conference of the Polymer Processing Society (PPS))

Characterization of Fiber Dust Resulting from Recycling of Carbon Fiber-Reinforced Thermoplastics (CFRP) and Their Cell Toxicity - Hopp, Matthias; Tölle, Lisa; Monsé, C.; Rosenkranz, N.; Haibel, N.; Walter, D.; Bünger, J.; Westphal, G. (Journal of Material Science and Chemical Engineering)

Multimaterial Injection Moulding of Thermosets and Elastomers - Moritzer, Elmar; Scheiermann, Denis; Bellusova, Denisa; Klie, Benjamin; Giese, Ulrich (ScienceBG)

Spritzgießen hochtemperaturbeständiger Baugruppen aus Duromeren und Elastomeren - Moritzer, Elmar; Scheiermann, Denis; Bellusova, Denisa; Klie, Benjamin; Giese, Ulrich (Kunststoffland NRW)

Institutionen der Medienpädagogik: Schule und Medien - Herzig, Bardo (Handbuch Medienpädagogik)

Messtechnische Ermittlung der Strukurintensität bei spritzgegossenen, faserverstärkten Kunststoffen - Moritzer, Elmar; Netzband, Dennis; Ujma, Andreas

Moodle in der Hochschullehre: Struktur durch HTML-Code - Fiege, Amanda Sophie; Pape, Stefan (#MoodleKannMehr – nicht nur im Distanzunterricht!)

Protest von Rechts? Strategien neurechter bzw. rechtspopulistischer Akteure zur Aneignung diskursiver Positionen des Widerstands im sogenannten 'Dritten Reich' - Markewitz, Friedrich (Protest, Protestieren, Protestkommunikation)

Argumentieren im Widerstand - Markewitz, Friedrich (Sprache in Politik und Gesellschaft. Perspektiven und Zugänge)

Quantum Dot Molecule Devices with Optical Control of Charge Status and Electronic Control of Coupling - Bopp, Frederik; Rojas, Jonathan; Revenga, Natalia; Riedl, Hubert; Sbresny, Friedrich; Boos, Katarina; Simmet, Tobias; Ahmadi, Arash; Gershoni, David; Kasprzak, Jacek; Ludwig, Arne; Reitzenstein, Stephan; et al. (Advanced Quantum Technologies)
Keywords: Electrical and Electronic Engineering; Computational Theory and Mathematics; Condensed Matter Physics; Mathematical Physics; Nuclear and High Energy Physics; Electronic; Optical and Magnetic Materials; Statistical and Nonlinear Physics

Neue Polymerwerkstoffe - Der Schlüssel für die Industrialisierung - Klippstein, Sven Helge

Authentic Englishes.nrw – Developing and Using Interactive Teaching and Learning Materials on Varieties of English - Pape, Stefan; Fiege, Amanda Sophie; Mindt, Ilka (Selected Papers from the 2021 Conference of the German Association for the Study of English)

Theorie-Praxis-Relationierung im Praxissemester: Die Perspektive der Mentor*innen. Eine explorative Studie - Caruso, Carina; Neuweg, Georg Hans; Wagner, Marlene; Harteis, Christian (Zeitschrift für Erziehungswissenschaft)
In der Mehrheit der deutschen Bundesländer ist ein Langzeitpraktikum (Praxissemester) Bestandteil der Lehramtsstudiengänge. Es zielt insbesondere darauf, Theorie und Praxis miteinander in Beziehung zu setzen. Trotz der gewichtigen Rolle, die den Mentor*innen dabei zugeschrieben wird, ist deren Perspektive noch wenig untersucht. Die empirisch auffindbaren Unterschiede in der Betreuung Studierender könnten u. a. auf unterschiedliche Vorstellungen von der Beziehung zwischen Theorie und Praxis seitens der Mentor*innen zurückzuführen sein. Diese Vorstellungen interessieren in der im Folgenden dargestellten explorativen Interviewstudie, deren Daten einer strukturierenden Inhaltsanalyse unterzogen wurden. Nachstehenden Forschungsfragen wird nachgegangen: 1) Sind die Mentor*innen auf die Aufgabe der Verknüpfung von Theorie und Praxis vorbereitet? 2) Werden in den Erzählungen der Mentor*innen zu gelingenden und misslingenden Betreuungserfahrungen Theorie-Praxis-Relationierungsfiguren sichtbar, wenn ja, welche und zeigen sich Bemühungen der Verknüpfung von Theorie und Praxis? 3) Werden in den Erzählungen der Mentor*innen zur eigenen Lerngeschichte Theorie-Praxis-Relationierungsfiguren sichtbar, wenn ja, welche und welche relative Rolle spielt das Ausbildungswissen aus Sicht der Mentor*innen für die Entwicklung ihres Könnens? 4) Welches Wissensverständnis der Mentor*innen zeigt sich in den Transkripten und welche Relevanz wird Wissen im Vergleich zu Erfahrung, Reflexion von Erfahrung und Persönlichkeit zugeschrieben? Es zeigt sich, dass die Mentor*innen das Theorie-Praxis-Verhältnis in den Gesprächen selten thematisieren, die Begriffe „Wissen“ und „Können“ synonym verwenden und der Erfahrung für die Entwicklung von Können eine höhere Relevanz beimessen als dem didaktischen und pädagogischen Ausbildungswissen.
Keywords: Lehrer*innenbildung; Mentoring; Praxissemester; Professionalisierung; Theorie-Praxis-Relationierung

Öffnung der Blackbox Hochschullehre durch kollaborative Autoethnografie - Autor:innengruppe , AEDiL (Ethnografie der Hochschule)

Kollaborative Autoethnographien digitaler Praktiken. Eine konzeptionelle, methodische und theoretische Einführung zu einem Lehr-Forschungsprojekt im ersten Corona-Semester - Steinhardt, Isabel (DNGPS Working Paper)
Keywords: Open Science; kollaborative Autoethnographie

MapOSR - A mapping review dataset of empirical studies on Open Science - Lasser, Jana; Schneider, Jürgen; Lösch, Thomas; Röwert, Ronny; Heck, Tamara; Bluemel, Clemens; Neufend, Maike; Steinhardt, Isabel; Skupien, Stefan (F1000Research)
<ns3:p>Research that investigates respective researchers’ engagement in Open Science varies widely in the topics addressed, methods employed, and disciplines investigated, which makes it difficult to integrate and compare its results. To investigate current outcomes of Open Science research, and to get a better understanding on well-researched topics and research gaps, we aimed at providing an openly accessible overview of empirical studies that focus on different aspects of Open Science in different scientific disciplines, academic groups and geographical regions. In this paper, we describe a data set of studies about Open Science practices retrieved following a PRISMA approach to compile a literature review. We included studies from the Scopus and Web of Science databases with keywords relating to Open Science between the years 2000 and 2020, as well as a snowball search for relevant articles. Studies that did not investigate any aspect of Open Science, or weren’t peer-reviewed were excluded, resulting in a total of 695 remaining studies.<ns3:italic> </ns3:italic>The data set was collaboratively annotated to ensure intercoder reliability of the coded data.</ns3:p>
Keywords: Open Science

Qualitative und quantitative Inhaltsanalyse: digital und automatisiert. Eine anwendungsorientierte Einführung mit empirischen Beispielen und Softwareanwendungen - Schneijderberg, Christian; Wieczorek, Oliver; Steinhardt, Isabel
Zur Inhaltsanalyse gibt es bereits diverse Methodenbücher. Warum sollten Sie also genau das vorliegende Methodenbuch „Qualitative und quantitative Inhaltsanalyse: digital und automatisiert “lesen? Erstens schließt dieses Buch eine Lücke, der wir in der Lehre und bei Methodenworkshops immer wieder begegnet sind. Diese Lücke besteht darin, dass selten eine Übersicht über und Gegenüberstellung verschiedener Methoden der qualitativen und quantitativen Inhaltsanalyse gegeben wird. Zudem haben bisherige Lehr-und Methodenbücher in den Sozialwissenschaften teil-und vollautomatisierte Verfahren der Textanalyse noch nicht aufgegriffen und diese mit bereits etablierten Verfahren qualitativer und quantitativer Inhaltsanalyse verknüpft. Zweitens bietet dieses Buch im ersten Teil eine systematische und anwendungsorientierte Einführung zu den Grundlagen inhaltsanalytischer empirischer Sozialforschung. Im zweiten Teil werden detaillierte Anleitungen von digital unterstützten qualitativen inhaltsanalytischen Auswertungstechniken gegeben. Den teil-und vollautomatisierten quantitativen inhaltsanalytischen Auswertungstechniken widmet sich der dritte Teil des Buches. Bei digital unterstützten Verfahren werden Sie durch Software bei Ihrer Analyse unterstützt, beispielsweise bei der digitalen Organisation Ihrer Daten und bei der digitalen Durchführung der Auswertung. Bei teilautomatisierten Verfahren der Inhaltsanalyse nehmen Ihnen Software und Tools Teile der Datenanalyse ab, wohingegen bei vollautomatisierten Verfahren der gesamte Auswertungsprozess und oftmals auch die Datenbeschaffung durch Programme und Tools durchgeführt wird.
Keywords: qualitative Inhaltsanalyse; quantitative Inhaltsanalyse

Evaluating Accents of English in ELT Textbooks Used at German Secondary Schools - Scheiwe, Lisa (Anglistik)

Correction to: Changes in patterns of eating habits and food intake during the first German COVID-19 lockdown: results of a cross-sectional online survey - Bühlmeier, Judith; Frölich, Stefanie; Ludwig, Christine; Knoll-Pientka, Nadja; Schmidt, Börge; Föcker, Manuel; Libuda, Lars (European Journal of Nutrition)
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Age at menarche relates to depression in adolescent girls: Comparing a clinical sample to the general pediatric population - Hirtz, Raphael; Libuda, Lars; Hinney, Anke; Föcker, Manuel; Bühlmeier, Judith; Holterhus, Paul-Martin; Kulle, Alexandra; Kiewert, Cordula; Kuhnert, Ronny; Cohrdes, Caroline; Peters, Triinu; Hebebrand, Johannes; et al. (Journal of Affective Disorders)
Keywords: Psychiatry and Mental health; Clinical Psychology

An explicit symplectic approach to solving the wave equation in moving media - Inguva, Venkatesh; Feldmann, Nadine; Claes, Leander; Koturbash, Taras; Hahn-Jose, Thomas; Koutcherov, Vladimir; Kenig, Eugeny (Engineering Reports)
An explicit approach using symplectic time integration in conjunction with traditional finite difference spatial derivatives to solve the wave equation in moving media is presented. A simple operator split of this second order wave equation into two coupled first order equations is performed, allowing these split equations to be solved symplectically. Orders of symplectic time integration ranging from first to fourth along with orders of spatial derivatives ranging from second to sixth are explored. The case of cylindrical acoustic spreading in air under a constant velocity in a 2D square structured domain is considered. The variation of the computed time-of-flight, frequency, and wave length are studied with varying grid resolution and the deviations from the analytical solutions are determined. It was found that symplectic time integration interferes with finite difference spatial derivatives higher than second order causing unexpected results. This is actually beneficial for unstructured finite volume tools like OpenFOAM where second order spatial operators are the state-of-the art. Cylindrical acoustic spreading is simulated on an unstructured 2D triangle mesh showing that symplectic time integration is not limited to the spatial discretization paradigm and overcomes the numerical diffusion arising with the in-built numerical methods which hinder wave propagation.

"Ein Steuerzahler!" Tax education in der frühen Bundesrepublik - Schönhärl, Korinna (Ökonomie und Moral im langen 20. Jahrhundert. Eine Anthologie)

Reconciliation in Resignation: The 2015 Greek Referendum on the Lenders’ Conditions - Schönhärl, Korinna (Journal of European Integration History)

Mehrsprachigkeit: Aspekte von Forschung und Messung - Gövert, Andre; Havkić, Amra; Settinieri, Julia (Handbuch Mehrsprachigkeit)

Long-Term Memory Recursive Least Squares Online Identification of Highly Utilized Permanent Magnet Synchronous Motors for Finite-Control-Set Model Predictive Control - Brosch, Anian; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Untersuchung von Gefahrensituationen bei industriellen Absorption/Desorption-Prozessen mittels dynamischer Simulation - Bothe, Mike; Lutters, Nicole; Kenig, Eugeny Y.

Server Cloud Scheduling - Maack, Marten; Meyer auf der Heide, Friedhelm; Pukrop, Simon (Approximation and Online Algorithms)

Adjustment of AgCaLa Phases in a FeMn Matrix via LBM for Implants with Adapted Degradation - Krüger, Jan Tobias (crystals)

Atar-Gull o Una venganza africana de Lucio V. Mansilla: un drama del romanticismo transatlántico - Schlieper, Hendrik (El drama histórico en los romanticismos de España e lberoamérica. Procesos transnacionales de intercambio y renegociación de identidades. (Teoría y Práctica del Teatro, 29))

Knoten/Schreiben: Graffignys Lettres d’une Péruvienne und die transatlantische Schrift-Kultur-Debatte - Schlieper, Hendrik (Transatlantische Aufklärung. Erfahrungen von Identität und Alterität im 18. Jahrhundert)

The ‚Empire‘ Writes Back: Literarische Rekolonialisierungen im Frankreich des 18. Jahrhunderts (Prévost, Lesage, Fuzelier/Rameau) - Schlieper, Hendrik (200 Jahre Nationalphilologien. Von der Romantik zur Globalisierung)

Transatlantische Aufklärung. Einleitende Überlegungen - Schlieper, Hendrik; Roselli, Antonio (Transatlantische Aufklärung. Erfahrungen von Identität und Alterität im 18. Jahrhundert)